"A Question Everybody Danced Around": Gay Men Making Sense of Their Identities in Christian Colleges. Issue 5 (3rd September 2018) - Bailey, Lucy E.; Strunk, Kamden K.
Abstract : Despite broader social changes in attitudes and policies regarding lesbian, gay, bisexual, transgender, and queer (LGBTQ) people, the space available for gay students to develop and express their identities in Christian colleges provides only limited and fleeting relief because of the culture of heteronormativity central to their history and identity. Yet, in an era of enrollment competition in higher education, Christian colleges must navigate their traditional mission to preserve and advance the faith, changing cultural attitudes regarding LBGTQ people, and the financial realities facing contemporary institutions. This article draws from interviews with men who attended Christian colleges. First, we present their narratives to render the presence of LGBTQ people visible in these sites. Second, we seek to understand how these men made sense of their sexualities within educational cultures saturated with retention imperatives, institutional surveillance, and denominational ambivalence or hostility about LGBTQ persons. The men's narratives highlight the challenges they faced as "unfit subjects" (Pillow, 2004 ), their absorption of normative constructions of gender and sexuality governing their educational context, and the need for Christian colleges to better serve their gay students of faith.